Modelling the impact of climate change on runoff and sediment yield in Mediterranean basins: the Carapelle case study (Apulia, Italy) - Abdelwahab, Ossama M. M.; Ricci, Giovanni Francesco; Gentile, Francesco; De Girolamo, Anna Maria (Frontiers in Water, 2025)
IntroductionThis study analyzes the impact of climate change on streamflow and sediment yield in the Carapelle basin, a Mediterranean watershed located in the Apulia Region of Italy.MethodsThree climate model projections (CMCC, MPI, EC-EARTH) under the CMIP6 SSP2-4.5 scenario were bias-corrected and evaluated using statistical measures to ensure enhanced fit with observed data. The Soil and Water Assessment Tool (SWAT) model was implemented to simulate hydrology and sediment yield. The model was calibrated and validated using measured streamflow and sediment load data from 2004–2011, demonstrating satisfactory performance for both parameters. Baseline conditions (2000–2020) were compared with future projections (2030–2050).ResultsClimate projections for 2030-2050 indicated temperature increases up to 1.3°C and average annual rainfall decreases up to 38% compared to baseline. These changes resulted in reduced water yield and sediment load across all models. The CMCC model projected the highest reduction in mean annual flow (67%), with smaller reductions from MPI (35%) and EC-EARTH (7%). Correspondingly, sediment load reductions were 52.8% (CMCC), 41.7% (MPI), and 18.1% (EC-EARTH). Despite these overall reductions, spatial analysis revealed that soil erosion remained critical (sediment yield >10 t ha−1) in certain areas, particularly on steep slopes with wheat cultivation.DiscussionIntegrating climate considerations into water management strategies is essential to sustaining Mediterranean river basins under future climate conditions. Adaptation measures such as BMPs and NBSs should be implemented to reduce soil erosion and to mitigate climate change impacts.